Understanding uncontrolled eating after bariatric surgery: The role of excessive skin and body Image shame - de Lourdes, Marta (2022)
Excess skin and disordered eating behaviors are referred to as some of the major negative consequences of bariatric surgery as well as body image shame. This study sought to explore how discomfort with excessive skin, body image shame, psychological distress, eating-related psychopathology, and negative urgency interact to understand uncontrolled eating among woman submitted to bariatric surgery. A cross-sectional sample of 137 women was evaluated postoperatively through self-report questionnaires assessing discomfort with excess skin, body image shame, eating-related psychopathology, negative urgency, and uncontrolled eating in a hospital center in the north of Portugal. Pearson correlations and Structural Equation Modeling (SEM) were performed. Body image shame mediated the relationship between discomfort with excess skin and eating-related psychopathology. In turn, the relationship between eating-related psychopathology and uncontrolled eating was mediated by negative urgency. This study highlights the impact of excess skin and body image shame on eating behavior post-bariatric-surgery. Considering the proven impact of uncontrolled eating on weight-loss results post-surgery, understanding the mechanisms underlying this problem is highly important. Our findings provide helpful insight for multidisciplinary teams committed to providing care to bariatric patients struggling with body image and eating difficulties.